Tingkat Partisipasi dan Faktor yang Memengaruhi Partisipasi Peternak Dalam Asuransi Usaha Ternak Sapi (AUTS) di Kabupaten Banyumas - Agam Yunianto; Herman Sambodo; Barokatuminalloh Barokatuminalloh (J-MAS (Jurnal Manajemen dan Sains), 2022)
The high risk faced by breeders in their livestock requires agricultural insurance to minimize losses caused by diseases, accidents and other risks. Banyumas Regency is an area that implements Cattle Business Insurance (AUTS), but only 1.5 percent of cattle are included in AUTS. Therefore, this study aims to find out the level of participation of breeders in the Cattle Business Insurance (AUTS) program and analyze the factors that affect it in Banyumas Regency. The study used primary data. The population in this study is breeders who have followed and or are following Cattle Business Insurance (AUTS). Sampling using random sampling with the number of respondents as many as 40 people based on Taro Yamane. The analytical tools used are tabulations and multiple linear regressions. The results of this study show that the participation of breeders in following AUTS belongs to the medium category. Factors that statistically significant and positively affect the participation of farmers in AUTS are the type of cow, the level of education, the experience of the farm business, and income, while age has a negative effect. The implication of this study is the need for encouragement for farmers to be more active in a series of activities of the AUTS program through increasing awareness of the risks of cattle businesses being run. There needs to be assistance for breeders, especially the elderly, to be able to actively participate in AUTS activities. To overcome the low level of education and improve the experience of breeders, there needs to be an increase in ability through training and mentoring to improve the quality of breeders.